Abdominal Anatomy Tutorial Using a Medical Imaging Platform - Madeleine J. Marsland; Dunya Tomic; Pamela L. Brian; Michelle D. Lazarus (Association of American Medical Colleges, 2018)
Introduction Easing students' transition to the clinical environment is vital in medical education. For anatomy, this can be achieved by incorporating medical imaging. Most resources for study of imaging solely cover structural identification, which does not adequately prepare students to interpret imaging in clinical practice. This resource adds to a series of tutorials incorporating clinical applications of anatomy. Methods The tutorial was a self-administered PowerPoint that guided students through principles of abdominal anatomy. It integrated radiological images, including X-ray, computed tomography, and magnetic resonance imaging, plus clinical correlations and self-evaluation. It was evaluated as a review tool, using repeated-measures control/experimental design, on 100 Australian medical students in preclerkship years. Testing comprised knowledge-based questionnaires, a Likert self-efficacy scale, and open-ended evaluation questions. Results Results suggest the tutorial significantly improved direct knowledge (p < .001), as the experimental group's posttutorial test scores were superior for direct questions by 32% on average. This difference was particularly significant for short-answer and multiple-choice questions. Students' confidence with anatomy and imaging was enhanced. Discussion These results demonstrate the tutorial's strength as a review resource. Unlike our previous work, where students received tutorials alongside anatomy teaching, this tutorial was assessed after coursework completion with similar results. Direct knowledge significantly improved; however, indirect applications did not, perhaps due to complexity of the region. Nonetheless, the results reinforce the value of the series' tutorials as review tools, as well as adjunct tools alongside anatomy curricula. There is scope for further research into their use as stand-alone resources.